Pro-Inflammatory Signature in Decidua of Recurrent Pregnancy Loss Regardless of Embryonic Chromosomal Abnormalities - Wu, Zaigui; Wang, Miaomiao; Liang, Guanmian; Jin, Pengzhen; Wang, Peng; Xu, Yuqing; Qian, Yeqing; Jiang, Xiuxiu; Qian, Junbin; Dong, Minyue (Frontiers in Immunology, 2021)
Recurrent pregnancy loss (RPL), especially the unexplained RPL, is associated with the disruption of maternal immune tolerance. However, little is known about the immune status at the decidua of RPL with embryonic chromosomal aberrations. Herein, mass cytometry (CyTOF) was used to interrogate the immune atlas at the decidua which was obtained from 15 RPL women—six with normal chromosome and nine with chromosomal aberrations—and five controls. The total frequency of CCR2−CD11chigh macrophages increased, while CD39high NK cells and CCR2−CD11clow macrophages decrease significantly in RPL when RPLs were stratified, compared with controls. Pro-inflammatory subsets of CD11chigh macrophages increased, while less pro-inflammatory or suppressive subsets decreased statistically in RPL decidua whenever RPLs were stratified or not. However, CD11chigh NK and CD161highCD8+ T cells increased only in RPL with normal chromosome, while the inactivated and naive CD8+/CD4+ T cells were enriched only in RPL with chromosomal aberrations. A pro-inflammatory signature is observed in RPL decidua; however, differences exist between RPL with and without chromosomal abnormalities.